Innovations in osteosynthesis and fracture care. - Matthews, Stuart J E; Nikolaou, Vassilios S; Giannoudis, Peter V (Injury, 2008)
Over the years giant steps have been made in the evolution of fracture fixation and the overall clinical care of patients. Better understanding of the physiological response to injury, bone biology, biomechanics and implants has led to early mobilisation of patients. A significant reduction in complications during the pre-operative and post-operative phases has also been observed, producing better functional results. A number of innovations have contributed to these improved outcomes and this article reports on the advances made in osteosynthesis and fracture care.
Keywords: Fracture Fixation, Internal; Humans; Internal Fixators